Concentração produtiva e tecnológica no paradigma industrial flexível: a influência dos ativos intangíveis na competitividade das empresas multinacionais - Debaco, Eduardo Scotti (2000)
First, it was made a bibliographic revision when are searched the main theories of MNE's growth and her competitive strategies on markets where technology become a decisive factor. The results of that stage can be read in chapter 2, where are discussed the MNE's strategies, and in chapter 3, where are analyzed the technological collaboration between enterprises. The evolutionist approach is presented in fourth chapter, when the technical progress and the technological innovations are discussed. From this revision are constructed 4 hypotheses to be tested in confrontation with empirical data, presented in chapter 5. The evolutionist approach gets 2 hypotheses: the technological progress is cumulative and the enterprises from home countries where the national system of innovation is more efficient are more competitive. Other point tested is the consequences ofForeign Direct Investment (FDI). Finally, it is discussed the growth of strategic partnership and the consequences for industrial concentration. The three first hypotheses were tested with econometrics techniques and fourth hypothesis is analyzed qualitatively. The results of analyses can be searched in the fifth chapter and the conclusions, in sixth.